A Guide to the Project Management Body of Knowledge (PMBOK® Guide) -- Eighth Edition and the Standard for Project Management. - PMI, Project Management Institute. (PMBOK® Guide Series, 2026)
A Guide to the Project Management Body of Knowledge  (PMBOK®   Guide) remains the premier resource for project professionals around the world.The Eighth Edition is the most evidence-based and community-driven revision to date, shaped by nearly 48,000 data points, global practitioner insights, and two rounds of public feedback.